Measurement and Increase of Academic Resilience: A Systematic Literature Review - Permatasari, Fani Fitriani (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2023)
Academic resilience is considered an asset in human characteristics and is a psychological construction that can be observed in some individuals which explains success despite experiencing difficulties. Individuals with poor academic resilience are feared to be unable to adapt to change, demands, and disappointment due to academic problems. Academic resilience can be seen when individuals face problematic experiences and know how to deal with or adapt to them. Academic resilience is a topic that is increasingly being researched so that developments related to definitions, measurement tools and interventions are increasingly diverse. Increasing individual academic resilience can be done through intervention, one of which is through guidance and counseling services. This study aims to synthesize various concepts related to academic resilience and test the effectiveness of guidance and counseling services to increase academic resilience by using literature reviews from several relevant sources.